2008
DOI: 10.1242/jcs.026492
|View full text |Cite
|
Sign up to set email alerts
|

Differential trafficking of Kif5c on tyrosinated and detyrosinated microtubules in live cells

Abstract: Kinesin-1 is a molecular transporter that trafficks along microtubules. There is some evidence that kinesin-1 targets specific cellular sites, but it is unclear how this spatial regulation is achieved. To investigate this process, we used a combination of in vivo imaging of kinesin heavy-chain Kif5c (an isoform of kinesin-1) fused to GFP, in vitro analyses and mathematical modelling. GFP-Kif5c fluorescent puncta localised to a subset of microtubules in live cells. These puncta moved at speeds of up to 1 m seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
171
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(185 citation statements)
references
References 54 publications
11
171
2
1
Order By: Relevance
“…Tubulin modifications are important for the affinity of motors and thus intracellular transport of the cellular cargoes. It was shown that the molecular motor kinesin binds preferentially to deTyr-tubulin to efficiently transport cargo (50,51). Disruption of tubulin dynamics can cause mitochondrial dysfunction and lead to neurodegeneration (52).…”
Section: Discussionmentioning
confidence: 99%
“…Tubulin modifications are important for the affinity of motors and thus intracellular transport of the cellular cargoes. It was shown that the molecular motor kinesin binds preferentially to deTyr-tubulin to efficiently transport cargo (50,51). Disruption of tubulin dynamics can cause mitochondrial dysfunction and lead to neurodegeneration (52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, microtubules carrying posttranslational modifications, such as tyrosination/detyrosination, show preferential interactions with certain KIFs. KIF5C, for example, preferentially binds detyrosinated and acetylated microtubules (Dunn et al 2008). It was shown recently in fact that loss of the tubulin tyrosinase enzyme causes loss of neuronal polarity with many neurons elaborating multiple tau-positive processes (Konishi and Setou 2009).…”
Section: Trafficking Guidance Receptorsmentioning
confidence: 99%
“…Kinesin-1 shows more strong binding affinity to MT enriched by detyrosinated tubulin in vitro (Liao and Gundersen, 1998). In vivo, kinesin-1 preferentially binds to detyrosinated tubulin-rich MTs (Dunn et al, 2008). Kinesin-1 selectively accumulates in a future axon in early stage of neuronal growth (Jacobson et al, 2006).…”
Section: Detyrosination/tyrosinationmentioning
confidence: 99%